Corpus Toponymicum Bahiae: portal toponímico e estudo ecolinguístico da toponímia baiana - Santiago, Iago Gusmão (2025)
This thesis consists of an ecolinguistic study of Bahian toponymy based on maps from the colonial period and the construction of a digital toponymic portal entitled Corpus Toponymicum Bahiae (www.ctbahiae.com/). The research's toponymic corpus is formed by the toponyms recorded in three maps from the colonial period, whose authorship has been attributed to the cartographer Anastasio de Santa Anna, with dates fixed in the years 1761 and 1807 (Havre, 2019), available in the Digital Collection of the National Library of Brazil (Acervo Digital da Biblioteca Nacional do Brasil). From an ecolinguistic point of view, this work discusses problems related to the traditional approach to toponymy, specifically Dickian classificatory principles (Dick, 1980; 1990; 1992), presenting a conceptual review and an alternative methodology based on ecolinguistics (Couto, 2007; 2009; 2013a; 2013b) and the principles of the rhizome by Deleuze and Guattari (1995). The toponymic portal initially comprises the Digital Archive of Historical Documents for Toponymic Studies (Acervo Digital de Documentos Históricos para Estudos Toponímicos - ADHET), which includes the edition of the basic documentation for feeding the portal's data, and the Historical Ecological Toponymic Dictionary of Bahia (Toponímico Histórico Ecológico da Bahia - DTHEB), a philologically based digital lexicographical work that seeks to be representative of Bahian toponymy from a linguistic, ecological, and historical point of view, encompassing the environments that condition the naming and use of toponyms. The resources explore the digital hypermedia environment, aiming to develop a product aligned with contemporary digital culture that can arise general interest, not just a specialized audience. This is an interdisciplinary work that converges reflections from the fields of digital and environmental humanities, establishing a bridge between toponymy, environmental preservation, and technology. This research is based on discussions in toponomastics, on the principles of ecolinguistics and environmental humanities, proposing a dialogue between the theoretical bases of the two areas in the articulation of a new line for toponymic studies in Brazil, which is called ecotoponomastics in this work, as well as philology and its interfaces with digital humanities. The qualitative ecolinguistic approach focused on 23 place names related to the toponymic network, objective and subjective environmental relationships between place names, involving the interaction between human and non-human animals. From this, the study observed the valorization of exploitation mechanisms when commercial factors are involved, as is the case with humancattle and human-whale interactions. With the construction of the toponymic portal, the research contributes to the development of toponymic studies in Brazil through a new methodological approach and the creation of a technological product capable of meeting the demands of higher and basic education, as well as stimulating/disseminating not only knowledge of Bahia's toponymic heritage, but also ecocentric thinking. In addition to the two products mentioned, ADHET and DTHEB, the platform intends to expand in the future to include the construction of a database, a digital toponymic atlas, and a digital library of educational resources, establishing a research agenda that ranges from working with basic documentation, through linguistic studies, and culminating in the dissemination and didactic transposition of the results.